Answer:
The sum of area of two smaller squares is equal to the area of bigger square
An equation using a, b, and c with exponents is
![c^2=a^2+b^2](https://img.qammunity.org/2021/formulas/mathematics/middle-school/byhrr90olo1xo4n215kg0bc367cjwlvx2c.png)
Explanation:
Let a be the side of the smallest square , b be the side of other smaller square and c be the side of biggest square
Area of square with side a =
![Side^2 = a^2](https://img.qammunity.org/2021/formulas/mathematics/high-school/ohqk9jmpbcu0sl7vr3g5s0ddtvmvwn04hh.png)
Area of square with side b =
![Side^2 = b^2](https://img.qammunity.org/2021/formulas/mathematics/high-school/hxy9ulzwxtrlk56hm4270y1y9vs5anvm5y.png)
Area of square with side c =
![Side^2 = c^2](https://img.qammunity.org/2021/formulas/mathematics/high-school/s55dhg9duj7dqdcnl0wfiknkkvafzwjfnv.png)
Refer the attached figure
In triangle ABC
![\angle A = 90^(\circ)](https://img.qammunity.org/2021/formulas/mathematics/high-school/lwz0v3kqls65f77do5p4odh0srckysl5gg.png)
So, We can use Pythagoras theorem over here
AB = a = Base
AC = b = Perpendicular
BC = c = Hypotenuse
![Hypotenuse^2=Perpendicular^2+Base^2\\c^2=a^2+b^2](https://img.qammunity.org/2021/formulas/mathematics/high-school/mbu7a3xeedyoof2pzpyxf62x27w5ujwmhh.png)
So, The sum of area of two smaller squares is equal to the area of bigger square
An equation using a, b, and c with exponents is
![c^2=a^2+b^2](https://img.qammunity.org/2021/formulas/mathematics/middle-school/byhrr90olo1xo4n215kg0bc367cjwlvx2c.png)